The potential role for ocrelizumab in the treatment of multiple sclerosis: current evidence and future prospects - Sorensen, Per Soelberg (Ther Adv Neurol Disord, 2016)
B cells play a central role in the pathogenesis in multiple sclerosis (MS), being involved in the activation of proinflammatory T cells, secretion of proinflammatory cytokines, and production of autoantibodies directed against myelin. Hence, the usage of B-cell-depleting monoclonal antibodies as therapy for autoimmune diseases including MS lay near at hand. Rituximab was the first therapeutic B-cell-depleting chimeric monoclonal antibody to be used successfully in MS. Ocrelizumab, a second-generation humanized anti-CD20 antibody, was explored in a large phase II, randomized, placebo-controlled multicentre trial in patients with relapsing–remitting disease. Compared with placebo, two doses of ocrelizumab (600 and 2000 mg on days 1 and 15) showed a pronounced effect on disease activity seen in magnetic resonance imaging (MRI) as gadolinium-enhanced lesions (89% and 96% relative reduction, both p < 0.001) and also had a significant effect on relapses. In exploratory analyses, both doses of ocrelizumab had better effect on gadolinium-enhanced lesions than interferon beta-1a intramuscularly that was used as a reference arm. Adverse effects were mainly infusion-related reactions, in particular during the first infusion. Serious infections occurred at similar rates in ocrelizumab and placebo-treated patients, and no opportunistic infections were reported. However, progressive multifocal leukoencephalopathy (PML) has been reported in patients treated with anti-CD20 monoclonal antibodies for other indications. Other anti-CD20 monoclonal antibodies have been tested as treatments for MS, including ofatumumab that has shown beneficial results in placebo-controlled phase II trials in patients with relapsing–remitting MS. Ocrelizumab is now in phase III development for the treatment of relapsing–remitting MS, as well as primary progressive MS, and the results of ongoing clinical trials are eagerly awaited and will determine the place of ocrelizumab in the armamentarium of MS therapies.